International criminal justice and the politics of compliance - Lamont, Christopher (Ashgate)
International criminal tribunals : the politics of state compliance -- Croatia : a coercive model for compliance -- Serbia : the politics of defiance -- Macedonia : voluntary compliance -- Bosnia-Herzegovina : compliance under diffuse sovereignty -- United Nations interim mission in Kosovo : international justice in an international protectorate